1997
DOI: 10.1002/ceat.270200302
|View full text |Cite
|
Sign up to set email alerts
|

Formation of emulsions in a screw loop reactor

Abstract: The following article concerns emulsification reaction in a continuous screw loop reactor. The influence of hydrodynamics on the emulsification process as well as the influence of some specific substances were examined. We produced oil/water model emulsions under different test conditions and we determined the correlations between the mixing behavior of the reactor and the characteristic features of the obtained emulsion. Special consideration was given to the droplet size and its distribution. Variable operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The span increases linearly with dispersed phase viscosity, and is well correlated with an R 2 of 0.949. At 9.4 mPa s the span averaged at 1.08 over a range of rotor speeds, rising to 3.18 at 969 mPa s. A broadening of the drop size distribution was also found by Ludwig et al (1997) for increasing m d . The width of the distribution increases greatly as the size of the largest droplet increases and there is also a growing formation of smaller droplets seen with increasing oil viscosity (Fig.…”
Section: The Effect Of Rotor Speed On Droplet Sizementioning
confidence: 68%
See 4 more Smart Citations
“…The span increases linearly with dispersed phase viscosity, and is well correlated with an R 2 of 0.949. At 9.4 mPa s the span averaged at 1.08 over a range of rotor speeds, rising to 3.18 at 969 mPa s. A broadening of the drop size distribution was also found by Ludwig et al (1997) for increasing m d . The width of the distribution increases greatly as the size of the largest droplet increases and there is also a growing formation of smaller droplets seen with increasing oil viscosity (Fig.…”
Section: The Effect Of Rotor Speed On Droplet Sizementioning
confidence: 68%
“…Ludwig et al (1997) found the drop size to be slightly higher for higher flow rates, while Thapar (2004) obtained smaller drop sizes at higher flow rates; however, both effects were diminished at higher rotor speeds. Thapar (2004) 3.4.…”
Section: The Effect Of Rotor Speed On Droplet Sizementioning
confidence: 73%
See 3 more Smart Citations